Association of β-Thalassemia and its Types with ABO and Rh Blood Groups in Pakistan - Waqar Mushtaq, Saadia Anwar, Safwan Ahmad, Kiran Kanwal, Shafaq Aziz, Inamullah Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: β-Thalassemia is a common inherited blood disorder in Pakistan, with considerable clinical and genetic heterogeneity. Exploring its association with ABO and Rh blood group systems may help uncover patterns that support early identification and management strategies. Objective: To determine the association between β-thalassemia and its subtypes with ABO and Rh blood group distributions in a cohort of Pakistani patients. Methodology: This cross-sectional study was conducted at The Children's Hospital Lahore from Feb 2023 to July 2023 and included 85 diagnosed β-thalassemia patients. Demographic details including age and gender, clinical characteristics such as the type of β-thalassemia (major, intermedia, or minor), consanguinity status, and family history of thalassemia were recorded. Results: Among 85 β-thalassemia patients, blood group B was most common (36.5%), followed by O (30.6%), A (24.7%), and AB (8.2%). Rh-positive status was observed in 91.8% of cases. No statistically significant association was found between ABO or Rh blood groups and thalassemia subtypes (p > 0.05). Consanguinity and family history were significantly higher in β-thalassemia major patients (p < 0.01). Conclusion: It is concluded that there is no significant correlation between β-thalassemia subtypes and ABO or Rh blood group systems. However, the predominance of blood group B and Rh-positive status among β-thalassemia patients aligns with trends observed in the general population. Further large-scale studies are recommended to validate these findings. Keywords: β-Thalassemia, patients, Rh distribution, ABO, Blood group